Implementation Ways and Risk Analysis of Big Data Analysis in the Construction of Labor Education in the New Era - Chang, Sendong; Luo , Gang; Li, Xian; Tan, Wuquan; Ping, Yang (Transactions on Social Science, Education and Humanities Research, 2024)
The arrival of the era of big data, also in the objective promoter of labor education courses in colleges and universities, plays an important role in college labor education course innovation development, under the new era background, to give full play to the big data era, with the help of big data technology and management advantages, innovation of labor education curriculum system, optimization of labor education teaching link, for labor education curriculum construction stable development vitality. In this paper based on big data horizon, the big data analysis in the new era of university labor education course construction in the implementation of the way and risk analysis, fully tap big data into the labor education course education teaching management application value, explore the background of the implementation of university labor education course teaching management innovation path.